cotx cot2x - cot2x cot3x-cot3x cotx=1

Here's the easiest method.

Find out, what's the biggest angle here? It's "cot 3x"

cot (3x) = cot ( 2x+x )

Apply, cot (A+B) = (cot A.cot B -1)/ cot A + cot B

So,

cot (3x) = ( cot 2x.cot x - 1 ) / cot 2x + cot x

Now, cross multiply

cot 3x ( cot 2x + cot x ) = cot 2x.cot x - 1

cot 2x.cot 3x + cot x.cot 3x = cot 2x.cot x - 1

cot 2x.cot x - cot 2x.cot 3x - cot x.cot 3x = 1

This is by far the easiest method, I've came across.

This method is applicable for both tan and cot..! :) 

Hope I helped..!! :D


  • 134

this is the answer

  • 30

hence proved

hence proved

  • 42
What are you looking for?